Deterrence and Influence in Counterterrorism A Component in the War on al Qaeda - Davis, Paul K. (RAND Corporation, 2002)
It may not be possible to deter fanatical terrorists, but members of terrorist systems may be amenable to influence. The U.S. counterterrorism strategy should therefore include political warfare, placing at risk things the terrorists hold dear, a credible threat of force against states or groups that support acquisition of weapons of mass destruction, and maintaining cooperation with other nations engaged in the war on terror, while also preserving core American values.